Splenic differentiation and emergence of CCR5+CXCL9+CXCL10+ monocyte-derived dendritic cells in the brain during cerebral malaria - Isabella C. Hirako (Nature Portfolio, 2016)
Cerebral malaria is an often fatal complication ofPlasmodium infection involving accumulation of inflammatory leukocytes in the central nervous system. Here the authors map the development and trafficking of CCR5+ monocyte-derived dendritic cells from the spleen to the brains of Plasmodium bergheiANKA infected mice.